2018
DOI: 10.1155/2018/2363917
|View full text |Cite
|
Sign up to set email alerts
|

Foxc2 and BMP2 Induce Osteogenic/Odontogenic Differentiation and Mineralization of Human Stem Cells from Apical Papilla

Abstract: As a transcription factor regulated by bone morphogenetic protein 2 (BMP2), Forkhead c2 (Foxc2) plays a pivot role in osteogenesis/odontogenesis. However, the role of Foxc2 and BMP2 in regulating osteo-/odontogenic differentiation and mineralization of stem cells from apical papilla (SCAP) is still uncertain. In this research, overexpression of Foxc2 gene significantly improved the proliferation of SCAP four days and eight days after transfection, but overexpression of both Foxc2 and BMP2 genes significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…On the contrary, frequent mitotic events can be observed in cells transfected with FOXC2 native sequence, demonstrating that the transcription factor is involved in cell proliferation. This result agrees with a great deal of previously reported evidence attesting the key role of FOXC2 in promoting the proliferation of tumor cells in vitro and in vivo [36][37][38]. It has also been shown that wild type FOXC2 can induce expression of several cell cycle regulators, including cyclin-dependent kinase 1 (CDK1) [19].…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, frequent mitotic events can be observed in cells transfected with FOXC2 native sequence, demonstrating that the transcription factor is involved in cell proliferation. This result agrees with a great deal of previously reported evidence attesting the key role of FOXC2 in promoting the proliferation of tumor cells in vitro and in vivo [36][37][38]. It has also been shown that wild type FOXC2 can induce expression of several cell cycle regulators, including cyclin-dependent kinase 1 (CDK1) [19].…”
Section: Discussionsupporting
confidence: 92%
“…BMP2, a member of the TGF-β family of proteins, contributes to odontogenic differentiation in DPSCs [18, 19]. Consistent with KEGG pathway data, BMP2, BMPR1, and phosphorylated Smad1/5/9 amounts were significantly increased in DPSCs incubated in Mg 2+ -enriched odontogenic media.…”
Section: Discussionmentioning
confidence: 60%
“…As reported previously, BMP2 is a TGF-β family member controlling odontogenic differentiation of stem cells [18, 19]. To verify the above KEGG pathway data, we performed Western blot to determine whether BMP2/Smads signaling is activated by high extracellular Mg 2+ .…”
Section: Resultsmentioning
confidence: 82%
“…Furthermore, there are a large number of studies investigating the influence of molecules on the directed differentiation of SCAPs. The osteo/odontogenic differentiation of SCAPs can be promoted by forkhead c2 [37], bone morphogenetic protein 2 ( BMP2) [3739], BMP9 [32, 40], SH3 and multiple ankyrin repeat domains 2 [25], GATA binding protein 4 [41], 17 β -estradiol [28], nuclear factor I-C [42, 43], secreted frizzled-related protein 2 (SFRP2) [44, 45], WD repeat domain 63 [34], insulin-like growth factor-1 [30, 46], recombinant human plasminogen activator inhibitor-1 [26], Rac1 gene [31], early growth response gene 1 [47], sirtuin 1 [48], potassium phosphate monobasic [49], canonical NF-kappaB signaling pathway [27], wnt/ β -catenin signaling [50], and some dentin-derived proteins [51]. By contrast, microRNA hsa-let-7b [52] and sonic hedgehog signaling [53] are able to inhibit this differentiation of SCAPs.…”
Section: Multilineage Differentiationmentioning
confidence: 99%